Exploring functional InDels and genetic diversity: agro-morphometric and molecular insights into the Western and Eastern gene pools of carrot (Daucus carota L.) - Mudihal, Trupthi; Cholin, Sarvamangala; Kulkarni, Chaitra C.; Shivaprasad, K. M.; Kumar, Prakash; Rolling, William; Simon, Philipp (Frontiers in Plant Science, 2025)
Carrot (Daucus carota L.) is a globally cultivated root vegetable with significant genetic diversity. This first study generated and validated carrot InDels to unravel the genetic divergence between Eastern and Western gene pools, integrating agro-morphometric traits with functional InDel markers. Eastern accessions exhibited larger plants, bigger roots with diverse colors, while Western accessions were more uniform orange color and compact in architecture. From RNA-seq data, 271 agarose-resolvable functional InDels (>15bp length difference) were identified, of which 48 validated markers showed high polymorphism (84.21%) across two gene pools supporting secondary domestication changes. Located in coding and UTR regions, these InDels likely regulate gene expression and may have contributed to significant genetic modifications among carrot gene pools. Genetic diversity in the Western gene pool indicated more intense selection and domestication. Population structure and phylogenetic analysis revealed clear gene pool differentiation (Fst = 0.181) with potential gene flow (Nm = 1.716). Functional annotation of linked InDels to key biological processes, highlighted their role in domestication. Key InDels (DcFInDel32, DcFInDel28, and DcFInDel55) were associated with multiple traits, underscoring their utility in marker-assisted selection (MAS). These findings provide insights for developing improved carrot cultivars with high yield and quality adapted to diverse climates.